Kinerja Perusahaan Dan Keselarasan Strategi Dengan Intensitas Persaingan Dan Kecanggihan Praktik Akuntansi Manajemen - Sekar Akrom Faradiza (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
In order to improve and maintain its competitive advantage, the company must choose the right strategy so that the expected performance can be achieved. But the right strategy is not enough, because the important factor that determines the performance is the alignment between strategy and its contingency variables. This study aimed to examine whether the performance of manufacturing companies in Indonesia is influenced by the alignment of strategy with the variable contingency, consist of competition intensity and sophistication of management accounting practices. Cluster Analysis is used to assess the sophistication of management accounting practices. This research used three-way ANOVA to examines strategy alignment and its effect on performance. The results indicate that the performance of manufacturing companies in Indonesia is not influenced by the alignment of strategy with the variable contingency.